Insights into the Regulatory Domain of Cystathionine Beta‐Synthase: Characterization of Six Variant Proteins. Issue 10 (31st July 2014) - Mendes, Marisa I. S.; Santos, Ana Sofia; Smith, Desirée E. C.; Lino, Paulo Roque; Colaço, Henrique G.; de Almeida, Isabel Tavares; Vicente, João B.; Salomons, Gajja S.; Rivera, Isabel; Blom, Henk J.; Leandro, Paula
<x xml:space="preserve">Abstract</x> We studied six missense mutations affecting the C‐terminal regulatory domain of CBS, an enzyme allosterically activated by SAM. We found that these variants presented a high residual enzyme activity and no changes in the kinetic parameters. Although lacking SAM activation some variants were able to bind SAM confirming that SAM activation and binding can be two independent events. At the structural level the variants showed various effects. Our studies highlight the relevance of SAM to maintain homocysteine homeostasis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>